Peran Multimedia Interaktif Dalam Pembelajaran Matematika Terhadap Hasil Belajar Siswa Kelas VIII di SMP Negeri 3 Mesuji - Septiana, Kadek Dwi; Yulianti, Dwi; Herpratiwi, Herpratiwi (Universitas PGRI Madiun, 2022)
Today's technology is an important instrument in the learning process. The development of ICT is very broad, therefore it needs to be utilized as much as possible. Educational technology tools, namely multimedia, are a combination of several media that are used as supporting tools in the learning process. The purpose of this study was to describe the role of interactive multimedia in learning mathematics to improve student learning outcomes for class VIII at SMP Negeri 3 Mesuji. The research method used is a quasi-experimental method with Group Pretest-Postets Control Design. The population in this study were all eighth grade students of SMP Negeri 3 Mesuji, totaling 62 students divided into three study groups. The sample in this study was class VIII.A totaling 32 students who were used as the experimental class and class VIII.B totaling 30 students who were used as the control class. Based on the results and discussion, it is concluded that the role of interactive multimedia in mathematics learning for class VIII SMP Negeri 3 Mesuji is effective to be applied in the learning process that can improve student learning outcomes